Two-dimensional metal organic framework Fen (bim) 2n packaged gas sensor and preparation method thereof
The two-dimensional metal-organic framework Fen(bim)2n, prepared by ammonia-assisted chemical vapor deposition, was used as the encapsulation layer for a MoS2 gas sensor, which solved the problem of decreased sensing performance under high humidity and achieved high sensitivity and reversibility of nitrogen dioxide detection.
Patent Information
- Application Number
- CN202511740197.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-25
- Publication Date
- 2026-03-20
AI Technical Summary
Existing two-dimensional materials are sensitive to humidity disturbances under high humidity conditions, which leads to a decrease in gas sensing performance and makes it difficult to accurately detect harmful gases at high humidity and room temperature.
A two-dimensional metal-organic framework Fen(bim)2n was prepared by ammonia-assisted chemical vapor deposition and used as the encapsulation layer of a MoS2 gas sensor. Its hydrophobic and porous properties reduced the influence of water molecule adsorption and enhanced the sensing performance.
It achieves reversible, rapid and highly sensitive detection of nitrogen dioxide at room temperature and high humidity, reduces the influence of water molecules on the sensor, and improves the sensor's moisture resistance.
Smart Images

Figure CN121699175A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gas detection technology, specifically relating to a two-dimensional metal-organic framework Fe n (bim) 2n Encapsulated gas sensor and its fabrication method. Background Technology
[0002] With the continuous advancement of global industrialization and changes in energy consumption patterns, the demand for air pollution monitoring has increased significantly. This is especially true for nitrogen oxides (NOx). x Harmful gases such as sulfur oxides (SO2), carbon dioxide (CO2), and fine particulate matter (PM2.5) seriously affect air quality, leading to environmental problems such as photochemical smog, acid rain, global warming, and climate change.
[0003] However, in real-world environments, relative humidity ranges from 20% to 80% RH (corresponding to 1200-4800 ppm at 0°C, but on the order of 14000-56000 ppm at 38°C), while the concentrations of gases typically detected are only in the tens of ppm or ppb levels. Under high humidity, water vapor competitively affects the specific adsorption of the target gas, making the detection of trace amounts of NO2 difficult. This manifests specifically as long-term baseline changes caused by humidity variations and a decrease in the response to ppm or ppb-level concentrations. Therefore, air humidity is a crucial factor that cannot be ignored in gas detection.
[0004] Currently, the main materials used in NO2 sensors are metal-oxide-semiconductor (MOS) and two-dimensional materials. MOS is widely used due to its high sensitivity, high response recovery speed, and low cost. However, MOS typically requires oxygen adsorption at high temperatures (usually 200℃-700℃) to achieve good gas sensing performance. Although high temperatures can reduce the performance degradation caused by water molecule adsorption, power consumption inevitably increases. In addition, MOS also suffers from poor selectivity. These drawbacks are significant reasons limiting the further widespread use of MOS materials in gas sensors.
[0005] Emerging two-dimensional materials, due to their large specific surface area and room-temperature sensing properties, are widely used in the detection of gases such as NO2. Two-dimensional metal-organic frameworks (MOFs) and transition metal sulfides of two-dimensional inorganic semiconductors (MoS2) are representative examples, both achieving good gas sensing performance at room temperature. However, when using two-dimensional MOFs themselves as the sensing layer, MOFs, due to their porous nature, have a higher specific surface area and more gas adsorption sites than two-dimensional inorganic semiconductors, making them more sensitive to humidity disturbances and subject to greater interference at high humidity levels. Therefore, using two-dimensional transition metal materials such as MoS2 as the sensing layer is more advantageous, as it not only possesses a large specific surface area and room-temperature sensing capabilities but also offers the outstanding advantage of adjustable bandgap and layer number for photoelectric performance.
[0006] In summary, while two-dimensional materials, such as MoS2, can achieve NO2 sensing at room temperature, their performance fluctuates and declines under humidity disturbances due to their large specific surface area and tendency to adsorb water molecules. Therefore, it is necessary to design a gas sensor that can accurately detect harmful gases at room temperature and high humidity (≥60%RH). Summary of the Invention
[0007] The present invention aims to at least solve one of the technical problems existing in the prior art. To this end, the present invention proposes a two-dimensional metal-organic framework Fe... n (bim) 2n Encapsulated gas sensors and their fabrication methods. This invention employs ammonia-assisted chemical vapor deposition to prepare two-dimensional metal-organic frameworks (Fe2O3). n (bim) 2n It was then used to encapsulate a MoS2 gas sensor, enabling reversible, rapid, and highly sensitive detection of nitrogen dioxide at room temperature and high humidity.
[0008] To address the aforementioned technical problems, a first aspect of the present invention provides a two-dimensional metal-organic framework Fe n (bim) 2n The preparation method, wherein the preparation method is an ammonia-assisted chemical vapor deposition method, specifically includes the following steps: (1) Mechanically peel off the mica sheets to obtain a fresh surface of the mica sheets; (2) Place the fresh surface of the mica sheet above benzimidazole and heat it to pre-evaporate a layer of benzimidazole on the fresh surface of the mica sheet; (3) Place ammonia water, the mica sheet obtained in step (2), and ferrocene in a reactor and introduce nitrogen gas; heat the reactor and, with the assistance of ammonia gas, grow the two-dimensional metal-organic framework Fe on the surface of the mica sheet. n (bim) 2n .
[0009] Specifically, this invention employs ammonia-assisted chemical vapor deposition to prepare two-dimensional metal-organic frameworks (Fe). n (bim) 2n First, a physical-mechanical exfoliation method was used to obtain fresh mica sheets. Then, benzimidazole was heated to form a high-purity benzimidazole pre-evaporation layer on the fresh surface of the mica sheets, which served as a ligand source. Next, ammonia water and ferrocene were heated to form an ammonia source and a metal source, respectively, and nitrogen gas was introduced to grow a two-dimensional metal-organic framework Fe on the surface of the mica sheets. n (bim) 2n The maximum size of this hydrophobic film can reach length × width × thickness = 75μm × 75μm × 22.4nm.
[0010] The hydrophobic Fe of the present invention n (bim) 2n The thin film growth method has at least the following advantages: in Fe n (bim) 2n During the growth process, the NH bonds in the benzimidazole ligand are primarily broken, allowing the iron ions in the ferrocene to coordinate with the nitrogen in the benzimidazole to form an ordered metallic framework structure linked by coordinate bonds. The addition of NH3 promotes the breaking of NH bonds, i.e., the deprotonation process, which further favors the growth of Fe. n (bim) 2n The growth of.
[0011] In some embodiments of the present invention, in step (2), the heating temperature is 180-220°C and the heating time is 20-30 min.
[0012] In some embodiments of the present invention, in step (3), the concentration of the ammonia water is 25-28%.
[0013] In some embodiments of the present invention, in step (3), the mass-to-volume ratio of ferrocene to ammonia is 10 mg: (3-5) mL.
[0014] In some embodiments of the present invention, in step (3), the ammonia water and ferrocene are placed in the first temperature zone and the second temperature zone of the reactor, respectively, and the mica sheet obtained in step (2) is placed between the first temperature zone and the second temperature zone. The temperature of the first temperature zone is 250-300℃, and the temperature of the second temperature zone is 100-120℃.
[0015] In some embodiments of the present invention, the growth time in step (3) is 5-15 min.
[0016] Experimental studies have found that both the concentration and growth time of ferrocene affect Fe. n (bim) 2nThe size and thickness, specifically manifested as: high ferrocene concentration and longer growth time will cause Fe n (bim) 2n The size is reduced, while the thickness is significantly increased (≥80 nm). Therefore, the low ferrocene concentration and short growth time contribute to the formation of large and thin hydrophobic two-dimensional Fe. n (bim) 2n .
[0017] A second aspect of the present invention provides a two-dimensional metal-organic framework Fe n (bim) 2n It is prepared by the above method.
[0018] A third aspect of the present invention provides a gas sensor, comprising an electrode, a MoS2 gas sensing layer, and a hydrophobic encapsulation layer, wherein the hydrophobic encapsulation layer is the aforementioned two-dimensional metal-organic framework Fe. n (bim) 2n .
[0019] Specifically, the two-dimensional metal-organic framework Fe prepared by this invention n (bim) 2n With its hydrophobic and porous properties, it can be used as a sealing layer in the MoS2 gas sensing layer, utilizing Fe... n (bim) 2n Its hydrophobic properties reduce the impact of water molecule adsorption. On the other hand, by utilizing its porous and high specific surface area, it can not only ensure that NO2 gas diffuses through to reach the sensing layer, but also compensate for the electrons lost by MoS2 after adsorbing NO2, thereby improving the sensor's sensing performance and moisture resistance.
[0020] In some embodiments of the present invention, the thickness of the hydrophobic encapsulation layer is 30-70 nm.
[0021] In some embodiments of the present invention, the thickness of the MoS2 gas sensing layer is 10-15 nm.
[0022] In some embodiments of the present invention, the gas sensor further includes a substrate, which may be made of materials commonly used in the art, such as SiO2 / Si substrates.
[0023] In some embodiments of the present invention, the electrode is an Au / Cr source / drain electrode, the channel length between the source and drain electrodes is 15-25 μm, the MoS2 gas sensing layer is located on the source / drain electrode channel, and the hydrophobic encapsulation layer covers the surface of the MoS2 gas sensing layer.
[0024] A fourth aspect of the present invention provides a method for preparing the above-mentioned gas sensor, comprising the following steps: 1) MoS2 nanosheets were dry-transferred onto the surface of the electrode using a mechanical exfoliation method to prepare an electrode containing MoS2 nanosheets; 2) With the assistance of water, the two-dimensional metal-organic framework Fe n (bim) 2n The material was transferred from the mica sheet to the polymer film and dried; then a two-dimensional metal-organic framework of the desired thickness, Fe, was selected. n (bim) 2n The gas sensor is fabricated by transferring the gas onto the MoS2 nanosheets.
[0025] Specifically, this invention employs physical-mechanical exfoliation and dry transfer, combined with water-assisted processing, to prepare Fe... n (bim) 2n / MoS2 gas sensor. Throughout the fabrication process, water-assisted transfer minimized reagent contamination and was simple and easy to perform, improving the cleanliness of the MoS2 nanosheet surface and thus better utilizing the material's intrinsic gas sensing performance.
[0026] In some embodiments of the present invention, step 1) of the electrode preparation containing MoS2 nanosheets includes the following steps: using adhesive tape to pick up MoS2 nanosheets, then transferring the molybdenum disulfide nanosheets onto a polymer film, then attaching the polymer film to the electrode, separating the polymer film, and obtaining MoS2 nanosheets by bonding them to the electrode through van der Waals forces.
[0027] In some embodiments of the present invention, step 1) further includes annealing the electrode containing MoS2 nanosheets at a temperature of 60-80°C for 1-3 hours to improve the contact between the MoS2 nanosheets and the electrode, which is beneficial to improving the electrical signal of the sensor.
[0028] In some embodiments of the present invention, the tape is Stoch tape.
[0029] In some embodiments of the present invention, the polymer film is polydimethylsiloxane (PDMS).
[0030] In some embodiments of the present invention, the two-dimensional metal-organic framework Fe n (bim) 2n The process of transferring from mica sheets to polymer films is as follows: For the growth of two-dimensional metal-organic frameworks (MOFs) on Fe... n (bim) 2nMica sheets were heated at 180-220℃ for 4-6 minutes to remove residual benzimidazole and ferrocene. PDMS was then applied to the mica sheets to ensure a tight bond (a tight bond is indicated by the sheets changing from white to translucent). The PDMS was slowly lifted to remove some thick layers and particles from the mica surface, repeating this process twice. For the third step, the PDMS was applied again and transferred to a petri dish containing deionized water. The PDMS was then slightly lifted at the interface, utilizing the hydrophilicity of the mica surface and the surface tension of water to separate the mica from the PDMS, revealing a thin layer of Fe. n (bim) 2n The material was transferred to PDMS. Note that the heating time for the mica sheets should not be too long, as prolonged heating can easily cause Fe... n (bim) 2n If the material adheres too tightly to the mica sheet, it will hinder the subsequent transfer to PDMS.
[0031] In some embodiments of the present invention, the required thickness of the two-dimensional metal-organic framework Fe n (bim) 2n The selection was performed using an optical microscope.
[0032] The fifth aspect of the present invention provides the application of the above-described gas sensor in detecting the concentration of nitrogen dioxide.
[0033] Specifically, the Fe of the present invention n (bim) 2n Under certain detection conditions, the / MoS2 sensor can reversibly, rapidly, and with high sensitivity detect extremely low concentrations of nitrogen dioxide at room temperature and humidity below 70%RH, with a minimum detection limit of less than 100ppb.
[0034] In some embodiments of the present invention, the process by which the gas sensor detects the concentration of nitrogen dioxide is as follows: first, Fe... n (bim) 2n The / MoS2 gas sensor applies voltage and a light source, and the gas to be measured is brought into contact with the gas sensor. By detecting the change in the electrical signal before and after the gas sensor comes into contact with the gas, the concentration of nitrogen dioxide in the gas to be measured can be obtained.
[0035] The concentration of nitrogen dioxide can be obtained by measuring the change in electrical signal at least through the following methods or other methods well known in the art: a standard curve or corresponding equation relating the change in concentration to concentration is obtained by detecting standard gases of different concentrations, and the concentration of the gas to be tested is obtained by substituting the detection result of the gas to be tested into the standard curve or the corresponding equation.
[0036] In some embodiments of the present invention, the voltage is 4-6V.
[0037] In some embodiments of the present invention, the gas sensor operates at a power density of 50-150 μW / cm². 2 The detection is performed under illumination conditions. The wavelength of the illumination is 400-450nm; preferably 400-440nm; more preferably 400-420nm; and even more preferably 400-410nm.
[0038] In some embodiments of the present invention, the electrical signal is a resistor.
[0039] In some embodiments of the present invention, the ambient temperature for detection is room temperature and the humidity is below 70%RH.
[0040] Compared with the prior art, the above-described technical solution of the present invention has at least the following technical effects or advantages: (1) This invention uses ammonia-assisted chemical vapor deposition to prepare two-dimensional metal-organic frameworks Fe n (bim) 2n In Fe n (bim) 2n During the growth process, the NH bonds in the benzimidazole ligand are broken, and the iron ions in the ferrocene coordinate with the N atoms in the benzimidazole to form an ordered metallic framework structure linked by coordinate bonds. The addition of NH3 promotes the breaking of the NH bonds, thus facilitating the preparation of Fe with hydrophobic and porous properties. n (bim) 2n .
[0041] (2) This invention utilizes a two-dimensional metal-organic framework Fe n (bim) 2n As a sealing layer for the MoS2 gas sensing layer, Fe is used n (bim) 2n The hydrophobic properties of MoS2 reduce the impact of water molecule adsorption; at the same time, its porous and high specific surface area allows NO2 gas to diffuse through to the sensing layer and compensate for the electrons lost by MoS2 after adsorbing NO2, thereby improving the sensor's sensing performance and moisture resistance.
[0042] (3) This invention uses mechanical exfoliation and dry transfer, combined with water assistance, to prepare Fe n (bim) 2n / MoS2 gas sensor. Throughout the entire preparation process, there is no reagent contamination, maximizing the intrinsic gas sensing performance of the material.
[0043] (4) The Fe of the present invention n (bim) 2nThe / MoS2 sensor can reversibly, rapidly, and with high sensitivity detect nitrogen dioxide in environments with room temperature and humidity below 70%RH, with a minimum detection limit of less than 100ppb. Attached Figure Description
[0044] Figure 1 The Fe prepared in Comparative Example 1 of this invention n (bim) 2n Optical microscope images.
[0045] Figure 2 The Fe prepared in Example 1 of this invention n (bim) 2n Optical microscope images.
[0046] Figure 3 The Fe prepared in Example 1 of this invention n (bim) 2n Thickness map obtained by atomic force microscopy.
[0047] Figure 4 The Fe prepared in Example 1 of this invention n (bim) 2n Contact angle test results.
[0048] Figure 5 This is an optical microscope image of the MoS2 gas sensor prepared in Comparative Example 2 of this invention.
[0049] Figure 6 The Fe prepared in Example 2 of this invention n (bim) 2n / MoS2 gas sensor optical microscope image.
[0050] Figure 7 The Fe prepared in Example 2 of this invention n (bim) 2n Fe in MoS2 gas sensor n (bim) 2n thickness.
[0051] Figure 8 This is a response curve of the gas sensors prepared in Example 2 and Comparative Example 2 of the present invention to 500 ppb NO2 at 70% RH humidity.
[0052] Figure 9 The Fe prepared in Example 2 of this invention n (bim) 2n / Response curve of MoS2 gas sensor to 100-500ppb NO2 at 70%RH humidity.
[0053] Figure 10These are response curves of the gas sensors prepared in Embodiment 2 and Comparative Example 2 of the present invention to 500 ppb NO2 under different humidity conditions.
[0054] Figure 11 The Fe prepared in Example 2 of this invention n (bim) 2n / MoS2 gas sensor response curve for 500ppb NO2 in 4 cycles at 70% RH humidity. Detailed Implementation
[0055] The present invention will now be described in detail with reference to embodiments to facilitate understanding of the invention by those skilled in the art. It is particularly important to note that the embodiments are merely illustrative of the invention and should not be construed as limiting the scope of protection of the invention. Non-essential improvements and adjustments made to the invention by those skilled in the art based on the above description should still fall within the scope of protection of the invention. Furthermore, all raw materials mentioned below, unless otherwise specified, are commercially available products; all process steps or preparation methods not mentioned in detail are process steps or preparation methods known to those skilled in the art.
[0056] Example 1 A hydrophobic two-dimensional metal-organic framework Fe2O3 grown by ammonia-assisted chemical vapor deposition n (bim) 2n The preparation method includes the following steps: (1) Cut the mica sheet into a rectangle with length × width = 25 × 8.33 mm, and peel it off repeatedly three times with Stoch tape to obtain a clean and fresh surface of the mica sheet.
[0057] (2) Prepare several 20mL sample bottles with a height of 57mm and an inner diameter of 17mm. Weigh 2g of benzimidazole ligand and put it into the sample bottle, spread it flat and compact it. Then, insert the freshly peeled mica sheet against the bottle wall with the ligand facing down, put the bottle cap on, and heat it at 200℃ for 20-30min to pre-evaporate a layer of benzimidazole on the fresh surface of the mica sheet.
[0058] (3) Take 4 mL of 25-28% ammonia water and 10 mg of ferrocene. Prepare a double-ended test tube with an outer diameter of 2 cm and a wall thickness of 1 mm. Cut a piece of aluminum foil to seal one end of the test tube. Place the ferrocene into the test tube sealed with aluminum foil on one side. Place the mica sheet obtained in step (2) obliquely on a right-angled triangular quartz stand with an inclination of 37° (dimensions are length × width × height = 15 × 8 × 8 mm, with an angle of 37° between the hypotenuse and the base). After assembling, place it together into the middle of the test tube 18.5 cm away from the ferrocene. Then place the test tube into a tube furnace with an inner diameter of 54 mm (outer diameter 60 mm, wall thickness 3 mm) and place 4 mL of ammonia water 35 cm away from the mica sheet. At this point, ferrocene is located in the second temperature zone of the tubular furnace, mica sheets are located at the boundary between the second and first temperature zones, and ammonia water is located at the front end of the first temperature zone. The temperatures of the first and second temperature zones are set to reach 285℃ and 105℃ respectively after 15 minutes. 10 sccm of N2 is introduced and the temperature is maintained for 5-15 minutes, resulting in the growth of the hydrophobic two-dimensional metal-organic framework Fe2O3 grown by ammonia-assisted chemical vapor deposition in this embodiment. n (bim) 2n Its optical microscope images are as follows Figure 2 As shown.
[0059] Figure 3-4 Fe prepared in Example 1 n (bim) 2n Optical microscope images, thickness maps measured by atomic force microscopy, and contact angle test results were obtained from... Figure 3-4 It can be seen that the hydrophobic two-dimensional metal-organic framework Fe grown using ammonia-assisted chemical vapor deposition... n (bim) 2n The length × width × thickness is 75μm × 75μm × 22.9nm; the contact angle is 112.9°, and it is a hydrophobic film.
[0060] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that step (3) does not contain ammonia, that is, the two-dimensional metal-organic framework Fe is grown without the assistance of ammonia. n (bim) 2n Its optical microscope images are as follows Figure 1 As shown.
[0061] Will Figure 1 and Figure 2 The comparison shows that, in the ammonia-free growth process, Comparative Example 1 only obtained a small amount of Fe with a length × width of 10 μm × 5 μm. n (bim) 2n Thin layer; while in Example 1, under the alkaline atmosphere formed by releasing ammonia gas from heated ammonia water at 60°C, a thin layer of Fe... n (bim) 2nThe size and yield are significantly improved, and a square white sheet with a length × width of 75μm × 75μm can be obtained.
[0062] Example 2 A Fe n (bim) 2n The method for fabricating a / MoS2 gas sensor includes the following steps: (1) Using Stoch tape and PDMS mechanically peeled off, 10-15 nm MoS2 nanosheets were obtained. MoS2 nanosheets of suitable size and thickness (10-15 nm) were found under an optical microscope. PDMS was attached to Au / Cr source and drain electrodes (the electrode substrate is SiO2 / Si) so that the MoS2 nanosheets are located in the channel (15-25 μm in length) between the source and drain electrodes. Then, PDMS was slowly lifted and MoS2 was transferred to the electrode surface by controlling van der Waals forces. Finally, the MoS2 gas sensor was annealed in a vacuum oven at 70 °C for 2 h to obtain the original bare MoS2 gas sensor.
[0063] (2) The hydrophobic two-dimensional metal-organic framework Fe prepared in Example 1 was grown. n (bim) 2n The mica sheet was heated at 200℃ for 5 minutes to remove residual benzimidazole and ferrocene. Then, PDMS was bonded to the mica sheet, and the PDMS was slowly lifted to remove some thick layers and contaminant particles from the mica sheet surface. This process was repeated twice. For the third time, after bonding the PDMS to the mica sheet, it was transferred to a petri dish containing deionized water. At the interface, the PDMS was gently lifted with pointed tweezers to allow water to seep into the edge. The hydrophilicity of the mica sheet and the surface tension of the water caused the PDMS to detach naturally from the mica sheet. At this point, a thin layer of Fe... n (bim) 2n It was transferred to PDMS.
[0064] (3) Use a bulb syringe to blow away any remaining water droplets on the PDMS, and locate the thin layer of Fe that needs to be transferred under an optical microscope. n (bim) 2n (Thickness 30-70 nm); then PDMS is attached to the electrode substrate of the transferred MoS2 nanosheets prepared in step (1), so that Fe n (bim) 2n The Fe in this embodiment is obtained by slowly lifting PDMS onto MoS2 nanosheets until it detaches from the electrode surface. n (bim) 2n / MoS2 gas sensor, its optical microscope image is as follows Figure 6 As shown. Figure 7 Its thickness was measured to be 34.1 nm using atomic force microscopy.
[0065] Comparative Example 2 The bare MoS2 gas sensor obtained in step (1) of Example 2.
[0066] Performance testing 1. Exposed MoS2 gas sensor The bare MoS2 gas sensor prepared in Comparative Example 2 was placed in a device equipped with a probe station, a humidifier, and a wavelength of 405 nm and a pressure of 75 μW / cm². 2 In a sealed gas test chamber irradiated by the light source, the humidity was raised to 70%RH, and a 5V DC voltage was applied through a Keithley 2450 impedance analyzer. After the electrical signal stabilized, 500ppb NO2 was introduced. Once the electrical signal on the Keithley 2450 analyzer reached saturation and stability, the sealed gas chamber was opened, allowing the introduced NO2 to desorb and escape from the surface of the gas sensor, thus restoring the initial electrical state in an atmospheric environment (70%RH).
[0067] Simultaneously, the response of the gas sensor to 500 ppb NO2 was tested under the same illumination conditions (40% RH and 55% RH humidity). After each test, the exposed MoS2 gas sensor was annealed at 60℃ for 1 hour to completely desorb NO2, preparing for the next test and the final Fe... n (bim) 2n / MoS2 is being prepared. Test results are as follows: Figure 8 and Figure 10 As shown, by Figure 10 It can be seen that no Fe is present at a humidity level of 40-70% RH. n (bim) 2n The response of the packaged bare MoS2 gas sensor dropped sharply from 2.82 to 0.53 as humidity increased.
[0068] 2. Fe n (bim) 2n / MoS2 gas sensor Using the same detection method described above, the Fe obtained in Example 2 was... n (bim) 2n The MoS2 gas sensor was placed in a sealed gas test chamber equipped with a probe station, humidifier, and 405nm light source. The humidity was raised to 70%RH, and a 5V DC voltage was applied using a Keithley 2450 impedance analyzer. After the electrical signal stabilized, 100-500ppb of NO2 with an air background was introduced into the test chamber, and Fe was measured. n (bim) 2n / MoS2 gas sensor at a power density of 75μW / cm 2The changes in electrical signals under 405nm illumination were studied. Specifically, the detection of 100ppb, 200ppb, 300ppb, 400ppb, and 500ppb NO2 was continuous, without the need for intermediate annealing. Annealing was performed at 60℃ for 1 hour after the 500ppb NO2 measurement was completed.
[0069] Meanwhile, using the same method described above, the response of the gas sensor to 500 ppb NO2 under the same illumination conditions (40% RH and 55% RH humidity) was tested, and the results are as follows: Figure 8 and Figure 10 As shown. (Through) Figure 9 The calibration curves fitting the response versus concentration were established, achieving a detection limit of 100 ppb for NO2. Figure 8 It can be seen that under high humidity of 70%RH, this Fe n (bim) 2n The MoS2 gas sensor only extended the response time τ. res With response time τ recs At that time, its overall signal-to-noise ratio and gas response are both improved.
[0070] Depend on Figure 10 It can be seen that the Fe n (bim) 2n The MoS2 gas sensor (Hetero) exhibits a stable response (1.03) at humidity levels ranging from 40% to 70%, representing nearly a 2x performance improvement compared to the original bare MoS2 gas sensor, which is significantly affected by humidity (from 0.53 to 1.03 at 70% RH). Meanwhile, the Fe... n (bim) 2n / MoS2 exhibits a uniform response value, and demonstrates excellent detection performance, especially under high humidity (70% RH). Therefore, this invention successfully provides a solution for a highly moisture-resistant NO2 gas sensor.
[0071] Figure 11 Fe prepared in Example 2 n (bim) 2n The response curve of the / MoS2 gas sensor to 500ppb NO2 in 4 cycles at 70% RH humidity is shown in the figure. Figure 11 It can be seen that, under high humidity of 70%RH, the gas sensor exhibits good repeatability and stability in response to the same concentration of NO2.
[0072] The change in electrical signal during the above detection process is the response value of the gas sensor. When the concentration of NO2 in the gas to be measured is unknown, the concentration of NO2 in the gas to be measured can be calculated based on this response value.
[0073] Figure 8-11The measured electrical signal is the change in resistance, expressed as Response = -1 + R. g / R a Given, where R g R is the resistance value of the sensor after gas is injected. a This represents the initial stable resistance value of the gas sensor. Fe prepared using the method of this invention... n (bim) 2n The / MoS2 gas sensor can successfully improve its sensing performance.
[0074] For those skilled in the art, several simple deductions or substitutions can be made without departing from the inventive concept, without requiring creative effort. Therefore, any simple improvements made to this invention by those skilled in the art based on the disclosure of this invention should be within the scope of protection of this invention. The above embodiments are preferred embodiments of this invention, and all processes similar to this invention and equivalent changes should fall within the scope of protection of this invention.
Claims
1. A two-dimensional metal-organic framework Fe n (bim) 2n The preparation method of the [method] is characterized by, The preparation method is ammonia-assisted chemical vapor deposition, which specifically includes the following steps: (1) Mechanically peel off the mica sheets to obtain a fresh surface of the mica sheets; (2) Place the fresh surface of the mica sheet above benzimidazole and heat it to pre-evaporate a layer of benzimidazole on the fresh surface of the mica sheet; (3) Place ammonia water, the mica sheet obtained in step (2), and ferrocene in a reactor and introduce nitrogen gas; heat the reactor and, with the assistance of ammonia gas, grow the two-dimensional metal-organic framework Fe on the surface of the mica sheet. n (bim) 2n .
2. The two-dimensional metal-organic framework Fe according to claim 1 n (bim) 2n The preparation method of the [method] is characterized by, In step (2), the heating temperature is 180-220℃ and the heating time is 20-30min.
3. The two-dimensional metal-organic framework Fe according to claim 1 n (bim) 2n The preparation method of the [method] is characterized by, In step (3), the concentration of the ammonia water is 25-28%; And / or, the ammonia water and ferrocene are placed in the first temperature zone and the second temperature zone of the reactor, respectively, and the mica sheet obtained in step (1) is placed between the first temperature zone and the second temperature zone. The temperature of the first temperature zone is 250-300℃, and the temperature of the second temperature zone is 100-120℃.
4. A two-dimensional metal-organic framework Fe n (bim) 2n Its characteristics are, It is prepared by the preparation method according to any one of claims 1-3.
5. A gas sensor, characterized in that, It includes electrodes, a MoS2 gas sensing layer, and a hydrophobic encapsulation layer, wherein the hydrophobic encapsulation layer is the two-dimensional metal-organic framework Fe as described in claim 4. n (bim) 2n .
6. The gas sensor according to claim 5, characterized in that, The thickness of the hydrophobic encapsulation layer is 30-70 nm; and / or, the thickness of the MoS2 gas sensing layer is 10-15 nm.
7. A method for preparing a gas sensor as described in claim 5 or 6, characterized in that, Includes the following steps: 1) MoS2 nanosheets were dry-transferred onto the surface of the electrode using a mechanical exfoliation method to prepare an electrode containing MoS2 nanosheets; 2) With the assistance of water, the two-dimensional metal-organic framework Fe n (bim) 2n The material was transferred from the mica sheet to the polymer film and dried; then a two-dimensional metal-organic framework of the desired thickness, Fe, was selected. n (bim) 2n The gas sensor is fabricated by transferring the gas onto the MoS2 nanosheets.
8. The method for preparing a gas sensor according to claim 7, characterized in that, In step 1), the preparation of the electrode containing MoS2 nanosheets includes the following steps: using adhesive tape to pick up MoS2 nanosheets, then transferring the molybdenum disulfide nanosheets onto a polymer film, then attaching the polymer film to the electrode, separating the polymer film, and thus obtaining the electrode.
9. The application of a gas sensor as described in claim 5 or 6 in detecting the concentration of nitrogen dioxide.
10. The application according to claim 9, characterized in that, The temperature measured was room temperature, and the ambient humidity was below 70%RH.